From Human Hands to Machine Algorithms: The Evolution of Byzantine Iconography in the Age of Artificial Intelligence - Tsiami, Zoe (Technical Annals, 2025)
Byzantine icons are sacred art forms that connect with the divine through meticulous techniques and deep symbolic types. Today, Artificial Intelligence (AI) introduces a new dimension to iconography, challenging traditional iconography. This presentation will explore the evolution from hand-painted icons, especially from the region of Selinon (Chania, Crete), to machine-generated interpretations. It will also discuss the philosophical implications of AI-generated Christian icons, questioning whether algorithms can capture the divine inspiration of human creators and their impact on religious societies. Furthermore, it will focus on the tradition of Orthodox iconography and its social importance in preserving it. This exploration highlights AI's potential to preserve and reimagine Byzantine iconography.